English Language Teaching in Inclusive Class: a Challenge - Desi Puspitasari (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2019)
Abstract Inclusive educational opens the door of the regular classrooms for the learners from different backgrounds. It gives students with special needs opportunity to learn equally as the other students. They also need to learn English as their foreign language. However, teaching inclusive classroom is not that easy. A number of challenges are faced by the English teachers during the teaching learning process. As teachers, they should realize their challenges and find the ways on how to overcome it, especially dealing with students with special needs. The aim of this paper is to determine the challenges faced by the English teachers. It also gives some insights on how to surmount the problems. It employs a qualitative study. This article argues that the English teachers have some challenges in teaching students with special needs. Thus, they need to concern in identifying the challenges they got and figure out the ways to solve it. Keywords: inclusive education, students with special needs, challenges, teaching English